Reflecting and Regretting - Avny, Ohad (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
This is the story of an elderly woman who suffers from dementia and has endured a lifetime of abuse from her husband. As the tale unfolds, we learn about this old woman’s tragic history, and of the attempts her doctor has made over the years to help her. The ethical issues the doctor struggles with, his emotions, as well as the strategic dilemmas he is forced to confront as he plans and manages the treatment and care of the husband and the wife create an unsettling backdrop to a story of patient and doctor behaviour. Ethical emotional and professional dilemmas when treating an abusive husband and his wife are discussed in detail.